Statins as modulators of bone formation - Edwards, Christopher J (BioMed Central, 2002)
The use of 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statins) to reduce serum cholesterol is well described. However, the recent finding that statins have direct effects on bone was unexpected. A number of epidemiological studies have recently been published that explore the effects of statins on bone mineral density and risk of fracture in humans. Statins may act by directly stimulating the expression of bone morphogenetic protein-2 and increasing osteoblast differentiation or, like nitrogen-containing bisphosphonates, may have effects on the mevalonate pathway that leads to inhibition of osteoclast activity and osteoblast apoptosis. In addition, the demonstration that statins can inhibit inflammation and encourage angiogenesis offers other possibilities for action.